Analisis Kepuasan Konsumen terhadap Kualitas Produk Beras PT Padi Indonesia Maju pada Retail Modern XYZ di Kabupaten Mojokerto - Fajar Tirto Sajiwo; Teguh Soedarto; Risqi Firdaus Setiawan (SAFE-Network, 2026)
Competition in the modern retail rice industry encourages companies to maintain product quality to increase consumer satisfaction. This study aims to identify consumer characteristics and analyze the level of consumer satisfaction with the quality of PT Padi Indonesia Maju rice products at XYZ modern retail in Mojokerto Regency. The study uses a quantitative approach with descriptive analysis methods. The sampling technique was carried out by purposive sampling which is the consumer of PT Padi Indonesia Maju rice products. Data were obtained through direct distribution of questionnaires to respondents. The results showed that the majority of respondents were aged 26-35 years, female, had a middle-income level, and had used the product for 6 months to 1 year. The results of the validity test showed that all research attributes were declared valid because the calculated r value was greater than the r table of 0.1654, while the results of the Reliability test showed a Reliability value of 0.70 at the actual level and 0.75 at the expected level so that the research instrument was declared reliable. The results of the Customer Satisfaction Index (CSI) calculation obtained a value of 77% which was in the satisfied category. The highest-rated quality attributes include rice cleanliness, conformity to product specifications, and texture, while shelf life still requires company attention. Companies need to improve quality control and maintain product consistency to maintain consumer loyalty and increase product competitiveness in modern retail.